(untitled) (Biological Sciences - PJSIR, 2010)
A new process developed for the preparation of naphthalene catechu tanning agent consisted of sulphonation of naphthalene, condensation with formaldehyde, combining with naturally occurring catechol, followed by neutral- ization of the reaction mixture. The product was then dried, analyzed and tested for application on wet blue leather which showed excellent tanning properties.